A Situational Analysis of EFL Textbook Selection in Thai Public Schools - Niwat Wuttisrisiriporn; Napanit Vinitchevit; Siriluck Usaha (Indonesian TESOL Journal, 2020)
It is undeniable that a textbook is a useful resource for teaching and learning. In English language education, especially in EFL countries, EFL teachers use a suitable EFL textbook to facilitate student learning. The present study, therefore, presents the current situation of how EFL textbooks are chosen as a core material in Thai public schools. An online questionnaire was distributed to 30 participants, who were English language teachers working at Thai public schools under the Office of the Basic Education Commission (OBEC). Interviews were also conducted to elicit more data from some of the participants. The findings of the study reveal that an EFL textbook is chosen based on whether it follows the Basic Education Core Curriculum, the textbook content, the textbook quality approval from the Ministry of Education, and price. However, the analysis shows that a systematic evaluation of an EFL textbook is not undertaken before the textbook is used, which can affect the teaching and learning outcomes in an EFL classroom. This paper proposes some recommendations regarding textbook evaluation criteria for those who are in charge of selecting a proper EFL textbook so that they can systematically evaluate and choose a practical textbook for their EFL classroom. It is also hoped to raise Thai EFL teachers’ awareness of the need for a proper textbook evaluation to be undertaken before a textbook is used in an EFL classroom.